2023
DOI: 10.1007/s11701-023-01677-w
|View full text |Cite
|
Sign up to set email alerts
|

Experience matters for robotic assistance: an analysis of case data

Abstract: Many robotic procedures require active participation by assistants. Most prior work on assistants’ effect on outcomes has been limited in procedural focus and scope, with studies reporting differing results. Knowing how assistant experience affects operating room time could inform operating room case scheduling and provide an impetus for additional assistant training. As such, this retrospective cohort study aimed to determine the association between assistant experience and operating room time for 2291 roboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…In this study, we found that BA with less than five years of experience did indeed lengthen the average operative time by approximately 29 min in line with a large retrospective study of 2,219 surgeries including prostatectomy, hysterectomy, and inguinal hernia repair, which showed that inexperienced BA prolonged operative time around 26.9 min [ 31 ]. However, in terms of postoperative complication, positive resection margin, intraoperative organ damage, lymph node dissection count, and hospital stays, we did not find any detrimental effects in the inexperienced BA 1 group or in learning phase of the learning curve.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we found that BA with less than five years of experience did indeed lengthen the average operative time by approximately 29 min in line with a large retrospective study of 2,219 surgeries including prostatectomy, hysterectomy, and inguinal hernia repair, which showed that inexperienced BA prolonged operative time around 26.9 min [ 31 ]. However, in terms of postoperative complication, positive resection margin, intraoperative organ damage, lymph node dissection count, and hospital stays, we did not find any detrimental effects in the inexperienced BA 1 group or in learning phase of the learning curve.…”
Section: Discussionsupporting
confidence: 79%